1976
DOI: 10.1128/jvi.17.1.191-203.1976
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Treatment of Ehrlich Ascites Tumor Cells: Effects on Exogenous mRNA Translation and tRNA Inactivation in the Cell Extract

Abstract: We reported earlier that in cell extracts that were prepared from interferontreated Ehrlich ascites tumor cells and preincubated and passed through Sephadex G-25 (S3OINT), the translation of exogenous mRNA (viral and host) was impaired and the impairment could be overcome to a large extent by adding a crude tRNA preparation from Ehrlich ascites tumor cells but not from Escherichia coli. We find now that the rate of inactivation of some tRNA's (especially those specific for leucine, lysine, and serine) but not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

1977
1977
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(10 citation statements)
references
References 43 publications
0
9
1
Order By: Relevance
“…Finally, it should be noted that inactivation of specific tRNA species leading to preferential elongation blocks has been suggested as a component of the antiviral mechanism induced by interferon (7,16,34,37,41,42). However, we have been unable to demonstrate any decrease in overall elongation rates which may be ascribed to interferon treatment alone in either mock-infected or EMC virus-infected cells.…”
Section: Discussioncontrasting
confidence: 64%
“…Finally, it should be noted that inactivation of specific tRNA species leading to preferential elongation blocks has been suggested as a component of the antiviral mechanism induced by interferon (7,16,34,37,41,42). However, we have been unable to demonstrate any decrease in overall elongation rates which may be ascribed to interferon treatment alone in either mock-infected or EMC virus-infected cells.…”
Section: Discussioncontrasting
confidence: 64%
“…The basic defect here was traced to an impairment of amino acid acceptor activity of lysyl-, seryl-, and, especially, of leucyl-tRNA's. This was due to a faster rate of inactivation of these tRNA forms in extracts from interferon-treated cells than from control cells (119).…”
Section: Evidence That Interferon Treatment Inhibitsmentioning
confidence: 92%
“…There were, however, some disturbing findings related to this neat explanation for interferon action (29,119). There was no difference in the amounts of tRNA from interferontreated or control cells required to correct the block in translation in extracts from interferontreated cells.…”
Section: Evidence That Interferon Treatment Inhibitsmentioning
confidence: 98%
“…It was found that translation in extracts of interferon-treated cells was more sensitive to inactivation by preincubation than was translation in control cells (69). This inactivation was shown to be a result of inactivation of transfer RNA (45,46,70,71,93,156,206) and could be overcome by the addition of a unique species of transfer RNA (71).…”
Section: Double-stranded-ribonucleic Acid-activated Enzyme Systemsmentioning
confidence: 99%